Analisis Minat Belajar Siswa Sekolah Dasar Swasta Kelas Tinggi Pada Mata Pelajaran Matematika - Winna Rahmayani (Simpati, 2023)
This study aims to analyze the learning interest of high class private elementary school students in Mathematics. Interest in learning is a key factor in student learning success, and a deep understanding of student interest in learning can help develop effective learning strategies. This study involved a sample of students from high class private elementary schools consisting of several age groups. Data was collected using a questionnaire specifically designed to measure students' interest in Mathematics. The questionnaire included questions regarding students' interest in the subject, confidence in solving mathematical problems, and students' perceptions of the relevance of mathematics in everyday life. The results of the data analysis showed that most of the high class private elementary school students had a negative interest in learning Mathematics. They have not shown high interest in this subject and have no strong confidence in solving math problems. In addition, students are also not aware of the relevance of Mathematics in their daily lives. It is hoped that the results of this research can provide valuable insights for educators and policy makers in increasing students' interest in learning Mathematics.